Pengaruh Tambahan Penghasilan Pegawai (TPP) Dan Disiplin Kerja Terhadap Kepuasan Kerja Pada Dinas Pekerjaan Umum Dan Penataan Ruang (PUPR) Kota Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2022)
ABSTRACTThis study aims to determine the effect of additional employee income (TPP) and work discipline on job satisfaction at the Palembang City Public Works and Spatial Planning Service (PUPR). The method used is a quantitative method with a sample size of 64 members. The data analysis technique used is multiple linear regression analysis, correlation coefficient, coefficient of determination, t test and F test. job satisfaction. While Work Discipline (X2) has a significant effect with a value of 0.000